2014
DOI: 10.1093/mnras/stu627
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bars on the M•-σe relation: offset, scatter and residuals correlations

Abstract: We analyse a set of collisionless disc galaxy simulations to study the consequences of bar formation and evolution on the M • −σ e relation of supermassive black holes (SMBHs). The redistribution of angular momentum driven by bars leads to a mass increase within the central region, raising the velocity dispersion of the bulge, σ e , on average by ∼12 per cent and as much as ∼20 per cent. If a disc galaxy with an SMBH satisfying the M • −σ e relation forms a bar, and the SMBH does not grow in the process, then … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 146 publications
(258 reference statements)
3
42
0
1
Order By: Relevance
“…Our previous image analysis improved upon this situation, and in our current larger sample we also have new galaxies with bars. Given that bars are known to elevate the velocity dispersion (Hartmann et al 2014), this result begs further investigation, possibly folding in disc inclination, bar orientation to our line-of-sight, and rotational velocity.…”
Section: Discussionmentioning
confidence: 87%
“…Our previous image analysis improved upon this situation, and in our current larger sample we also have new galaxies with bars. Given that bars are known to elevate the velocity dispersion (Hartmann et al 2014), this result begs further investigation, possibly folding in disc inclination, bar orientation to our line-of-sight, and rotational velocity.…”
Section: Discussionmentioning
confidence: 87%
“…Graham (2008a) similarly considered the offset galaxies to have undermassive black holes, due to secular evolution over-developing the bulge, or to have elevated velocity dispersions due to the dynamics of the bar. The choice appears answered because Hartmann et al (2014) have shown that bars are indeed capable of increasing the velocity dispersion in galaxies, and by exactly the average offset observed in the M bh -σ diagram (see also Debattista et al 2013 andMonari et al 2014). Furthermore, Figure 2 shows that pseudobulges and classical bulges (and clump bulges) follow the same broad distribution in the M bh -M sph diagram; at low spheroid masses they both reside systematically below the near-linear relation defined by the massive core-Sérsic spheroids.…”
Section: Substructure and Escalating Slopesmentioning
confidence: 99%
“…Contamination by dynamically distinct substructure is usually unavoidable, and rotational broadening due to disk contamination can strongly affect σ measurements from single-aperture spectra (e.g. Graham et al 2011;Hartmann et al 2014;Bellovary et al 2014, W13). In addition, Batiste et al (2017) (hereafter B17) showed that slit orientation relative to substructure, such as bars, can strongly affect the measured σ .…”
Section: Introductionmentioning
confidence: 99%